Atomic Layer Deposition for Coating of High Aspect Ratio TiO2 Nanotube Layers - Zazpe, Raul; Knaut, Martin; Sopha, Hanna; Hromádko, Luděk; Albert, Matthias; Přikryl, Jan; Gärtnerová, Viera; Bartha, Johann W.; Macák, Jan M. (American Chemical Society, 2016)
We present an optimized approach for the deposition of Al2O3 (as a model secondary material) coating into a high aspect ratio (≈180) anodic TiO2 nanotube layers using atomic layer deposition (ALD) process. In order to study the influence of the diffusion of the Al2O3 precursors on the resulting coating thickness, ALD processes with different exposure times (i.e. 0.5, 2, 5 and 10 sec) of the trimethylaluminium (TMA) precursor were performed. Uniform coating of the nanotube interiors was achieved with longer exposure times (5 and 10 sec), as verified by detailed scanning electron microscopy analysis. Quartz crystal microbalance measurements were used to monitor the deposition process and its particular features due to the tube diameter gradient. Finally, theoretical calculations were performed to calculate the minimum precursor exposure time to attain uniform coating. Theoretical values on the diffusion regime matched with the experimental results and helped to obtain valuable information for further optimization of ALD coating processes. The presented approach provides a straightforward solution towards the development of many novel devices, based on a high surface area interface between TiO2 nanotubes and a secondary material (such as Al2O3).
Keywords: TiO2; nanotubes; coating; ALD; diffusion